Acetyl‐ed question in mitochondrial biology?. (14th September 2015) - Lombard, David B; Dash, Banaja P; Kumar, Surinder
Abstract : Lysine acetylation on numerous mitochondrial proteins, targeted by the sirtuin deacylase SIRT3, has been proposed to play a major role in regulating diverse mitochondrial functions, particularly in the liver. A new study by Weinert, Choudhary, and colleagues, in this issue of The EMBO Journal, finds that the absolute levels of hepatic mitochondrial protein acetylation in wild‐type mice are extremely low and may be insufficient to exert regulatory effects. Abstract : New findings of very low acetylation stoichiometry on hepatic mitochondrial proteins question the widespread regulatory significance of SIRT3 deacylase‐targeted lysine acetylation in liver mitochondria.